Building better homes : government strategies for promoting innovation in housing - Hassell, Scott, 1974- (Santa Monica, CA : RAND, 2003)
This report examines the structure, characteristics, and motivations of major participants in the housing industry to explore how innovation might be accelerated. It identifies options and strategies for the federal government to consider as it attempts to further advance innovation in housing to make homes more affordable, durable, and safe. Housing is the largest component of the nation's physical wealth, representing nearly 20 percent of the nation's gross domestic product. Therefore, innovation in that industry would contribute positively to increase productivity and provide benefits t.
Innovation in housing -- The concept of innovation in the U.S. housing industry -- The U.S. housing industry as the context for innovation -- Industry characteristics and motives and their effect on innovation -- Federal efforts to promote innovation in housing -- Federal strategies for promoting innovation in housing.
"Prepared for the U.S. Department of Housing and Urban Development (HUD), Office of Policy Development and Research and the Partnership for Advancing Technology in Housing (PATH)."
Includes bibliographical references (pages 97-108).
Print version record.
eBooks on EBSCOhost
Keywords: Housing policy -- United States; Logement -- Politique gouvernementale -- États-Unis.; BUSINESS & ECONOMICS -- Real Estate -- General; TECHNOLOGY & ENGINEERING -- General; Housing policy; United States